The female Klebun of Madura within the power constellation of the patriarchy: A post-colonial feminism perspective - Aminah Dewi Rahmawati; Emy Susanti; Bagong Suyanto (Universitas Trunojoyo Madura, 2021)
During the Indonesian reformation era, Madurese politics began to see a notable increase in women participation. One indicator is the increasing number of female village chiefs, locally referred to as Klebun, who occupies the highest leadership position within Madurese villages. An in-depth interview with two female Klebuns and three informants revealed that female Klebun in Madura represents women and extended kinship interests in continuing dynastic politics. The female Klebun experienced a subaltern form of relationship with the largely patriarchal system they find themselves in, marked by coercion, threats, pressure and lack of freedom in their candidacy and village leadership. The lack of any communicated objections from the female population over these repressive actions is due to the strong dominance of patriarchal culture in Madurese society. This research uses a descriptive qualitative approach. The primary data used are the results of interviews with five informants. Secondary data used consist of relevant scientific journals, articles, and books. This research is conducted under the framework of postcolonial feminism.